2018
DOI: 10.1016/j.neuron.2018.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Volitional Modulation of Primary Visual Cortex Activity Requires the Basal Ganglia

Abstract: Animals acquire behaviors through instrumental conditioning. Brain-machine interfaces have used instrumental conditioning to reinforce patterns of neural activity directly, especially in frontal and motor cortices, which are a rich source of signals for voluntary action. However, evidence suggests that activity in primary sensory cortices may also reflect internally driven processes, instead of purely encoding antecedent stimuli. Here, we show that rats and mice can learn to produce arbitrary patterns of neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 79 publications
5
60
0
Order By: Relevance
“…For example, it has been demonstrated that the task-relevant modulation of indirect neurons gradually reduces relative to direct neurons as monkeys learn to control a BMI (Ganguly et al, 2011). Additionally, it has been shown in rodents that coherence develops between dorsal striatum and direct neurons, but not indirect neurons, as the animals improve control (Koralek et al, 2012(Koralek et al, , 2013Neely et al, 2018). In a separate study using 2-photon calcium imaging to record neural activity, it was shown that mice modulate activity of direct and indirect neurons in early learning, but eventually learn to mostly modulate activity of the direct neurons (Clancy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been demonstrated that the task-relevant modulation of indirect neurons gradually reduces relative to direct neurons as monkeys learn to control a BMI (Ganguly et al, 2011). Additionally, it has been shown in rodents that coherence develops between dorsal striatum and direct neurons, but not indirect neurons, as the animals improve control (Koralek et al, 2012(Koralek et al, , 2013Neely et al, 2018). In a separate study using 2-photon calcium imaging to record neural activity, it was shown that mice modulate activity of direct and indirect neurons in early learning, but eventually learn to mostly modulate activity of the direct neurons (Clancy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the extent to which this behavior is indeed goal-directed, a subset of mice underwent a contingency degradation test (Witten, et al, 2011;Koralek, et al, 2012;Clancy et al, 2014;Neely et al, 2018). During this test phase, stimulation was decoupled from the leverpressing action and instead delivered non-contingently at a rate yoked to that animal's own stimulation rate from the preceding self-stimulation phase (Methods).…”
Section: Actionmentioning
confidence: 99%
“…A contingency degradation test session began with 30 min of standard opto-ICSS (CRF for the CRF cohort, LR sequence task for the LR cohort). In the subsequent 30-min contingency degradation test phase, the levers remained extended, but stimulation was decoupled from task performance and instead was delivered regardless of whether the mice pressed any levers (Witten, Steinberg, et al, 2011;Koralek, Jin, et al, 2012;Clancy et al, 2014;Neely et al, 2018). For each mouse, the timing of these non-contingent stimulations during the test phase was matched to the time stamps of stimulations earned during that animal's preceding opto-ICSS phase in the first half of the session, ensuring that the stimulation rate and distribution of inter-stimulation intervals were yoked within-subject to a given animal's own opto-ICSS performance.…”
Section: Contingency Degradationmentioning
confidence: 99%
“…During neuroprosthetic skill acquisition in rodents, learning is accompanied by increased cortico-striatal communication evidenced by cortico-striatal coherence observed in the LFP (11), as well as spike field coherence (SFC) between cortical neurons and striatal oscillations and vice versa (10)(11)(12). Striatum is not a clinical target in iEEG recordings in epilepsy patients, and thus we were unable to test the hypothesis of striatal communication in the volitional control of individual neurons in humans.…”
Section: Spike-field-coherence Develops During Learningmentioning
confidence: 99%